Evaluating the Functional Role of Enhancing Progenitor Cell Survival Following Stroke Recovery - Ceizar, Maheen (Université d'Ottawa / University of Ottawa, 2017)
Stroke is the leading cause of long-term neurological disability worldwide, signifying the need for viable therapeutic options. Pre-clinical and post-mortem stroke studies have demonstrated that stroke increases the number of newborn progenitor cells (PCs) in the adult brain that can migrate to the site of injury. While there is a positive correlation between increasing neurogenesis and improvements in stroke recovery, methods used to increase PCs and neurogenesis also alter many other forms of plasticity, making it difficult to determine the function of PCs per se. To investigate whether specifically enhancing PC survival is sufficient to improve recovery, the iBax transgenic mouse model was used to remove the pro-apoptotic gene Bax inducibly from nestin-expressing PCs either before or after focal strokes induced by photothrombosis. Increasing PC survival before or after stroke in the iBax mice increased the number of PCs in the peri-infarct region. Interestingly, the majority of the cells that migrated to the peri-infarct region expressed the glial fibrillary acidic protein (GFAP) which is found in astrocytes when Bax was removed prior to stroke, yet when Bax was removed after stroke the majority of the cells expressed doublecortin (DCX) which is expressed in neuroblasts. Irrespective of this significant increase in the different populations of surviving PCs following stroke, there was no change in long-term behavioural deficits on the adhesive removal, horizontal ladder, and cylinder tasks up to 90 days post stroke. Additionally, enhancing PC survival before or after stroke resulted in a significant increase in adult-generated neurons within the dentate gyrus, which was associated with a modest change in spatial learning on the Barnes maze. Together, these experiments suggest strategies that enhance the survival of the PCs by preventing cell death will, by themselves, be insufficient to promote sensorimotor recovery following stroke.
Keywords: Stroke Recovery; Adult Neurogenesis